A tricky man issue: Angiokeratomas of scroti - Yugandar Inakanti; Thimmasarthi Venkata Narsimha Rao (Our Dermatology Online, 2015)
Angiokeratoma is a benign cutaneous lesion of capillaries, resulting in small marks of red to blue colour spots and characterized by hyperkeratosis. They often unnoticed, may become crusty and bleed if accidentally scratched or damaged. We presented our cases because of its apprehension, health anxiety created to patients by complaint it as malignancy of scrotum and sexually transmitted diseases. Most of patients seek medical advice to rule out sexually transmitted diseases and malignancy. The cases well highlights these unusual complaints of Angiokeratoma and only two reports of multiple Angiokeratomas available in an Indian Dermatology literature.